Integrative potential of Central European metropolises with a special focus on the Visegrad countries - Šauer, Martin; Pařil, Vilém; Viturka, Milan (Technological and Economic Development of Economy, 2019)
One of the characteristic phenomena associated with the current development of civilization is undoubtedly metropolisation. This article focuses on the strategically important problems of the metropolisation of the Central European area with an emphasis on the Visegrad countries. The introductory part is dedicated to the identification of Central European metropolises based on three components: population size, economic profile and investment attractiveness. Designated metropolises are then assessed from the point of view of integrative potential level, including economic interactivity, tourist attractiveness and transport connectivity. Based on the synthesis of these components, the most important axes of supranational importance were identified. It can be said that within the established network of metropolitan axes connecting eastern with western parts of the Central European region the Czech Republic is the best placed, followed by Poland. From a wider geopolitical outlook this network creates favourable conditions for the integration of the Visegrad countries, mainly driven by international trade.